Post synthetically modified IRMOF-3 for efficient recovery and selective sensing of U(vi) from aqueous medium. Issue 45 (19th August 2021) - Venkata Sravani, V.; Tripathi, Sarita; Sreenivasulu, B.; Kumar, Satendra; Maji, S.; Brahmmananda Rao, C. V. S.; Suresh, A.; Sivaraman, N.
Abstract : Four IRMOFs following PSM strategy were prepared. The MOFs were characterized by different techniques and were investigated for U(vi ) sorption. PSM MOFs displayed impressive fluorescent sensing and selectivity of U(vi ) over competing metal ions. Abstract : A simple and efficient route to develop various novel functionalized MOF materials for rapid and excellent recovery of U(vi ) from aqueous medium, along with selective sensing has been demonstrated in the present study. In this connection, a set of four distinct post synthetically modified (PSM) iso-reticular metal organic frameworks were synthesized from IRMOF-3 namely, IRMOF-PC (2-pyridine carboxaldehyde), IRMOF-GA (glutaric anhydride), IRMOF-SMA (sulfamic acid), and IRMOF-DPC (diphenylphosphonic chloride) for the recovery and sensing of U(vi ) from aqueous medium. The MOFs were characterized by Fourier transform infrared spectroscopy (FTIR), powder XRD, BET surface area analysis, thermogravimetric analysis (TGA), NMR ( 13 C, 1 H and 31 P), Scanning Electron Microscopy (SEM), and energy dispersive X-ray spectroscopy (EDX). Among all MOFs, post synthetically modified IRMOF-SMA showed enhanced thermal stability of about 420 °C. The MOFs were investigated for U(vi ) sorption studies using a batch technique. All the MOFs exhibit excellent sorption capacity towards U(vi ) (>90%) and maximum uptake was observed at pH 6. Sorption capacity of MOFs have the following order; IRMOF-3-DPC (300 mg U g −1 ) > IRMOF-SMA (292 mg U g −1 ) > IRMOF-PC (289 mg U g −1 ) > IRMOF-GA (280 mg U g −1 ) > IRMOF-3 (273 mg U g −1 ). IRMOF-DPC shows rapid sorption of uranium within 5 min with excellent uptake of U(vi ) (>99%). The desorption of U(vi ) was examined with different eluents and 0.01 M HNO3 was found to be most effective. The fluorescence sensing studies of U(vi ) via IRMOF-3 and its PSM MOFs revealed high sensitivity and selectivity towards U(vi ) over other competing rare earth metal ions (La 3+, Ce 4+, Sm 3+, Nd 3+, Gd 3+, and Eu 3+ ), wherein IRMOF-GA displayed an impressive detection limit of 0.36 mg L −1 for U(vi ).